Determinants of STI Risk Behaviors as a Function of Alcohol use and Incarceration History Among Male Adolescent Offenders - Torrance Stephens (Journal of Psychosexual Health)
Aims: The purpose of this analysis was to identify bivariate correlates of history of prior incarceration, and self-reported risky sexual practices among a sample of adolescent male detainees. Methods: The current analyses included 139 male adolescent offenders enrolled in an AOD/HIV prevention intervention conducted in a juvenile detention facility in a major Southeastern city in the USA. Significance tests were conducted using univariate logistic regressions to examine the independent associations of prior arrest history, and self-reported risky behaviors prior to this recent incarceration. Results: Adolescents who identified as having a prior arrest history were more likely to report they had willingly had sex with a prostitute (OR = 2.78, 95% CI = 1.29–5.95), used alcohol or other drugs to get a desired effect (OR = 3.39, 95% CI = 1.18–9.68), had tattoos (OR = 4.18, 95% CI = 1.78–9.78) and were addicted to AODs (OR = 2.51, 95% CI = 0.77–8.16). Conclusion: Findings suggest that risk practices that increase risk for STIs among adolescent male offenders, maybe a function of incarceration history.